2006
DOI: 10.1111/j.1572-0241.2005.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Predictors of Elevated Serum Aminotransferase Activity in the United States in 1999-2002

Abstract: The current prevalence of elevated ALT activity in the United States (8.9%) is more than double that of previously available estimates. This prevalence is very high (7.3%) even among persons without viral hepatitis C or excessive alcohol consumption and is strongly associated with risk factors for nonalcoholic fatty liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
211
7
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(246 citation statements)
references
References 11 publications
15
211
7
11
Order By: Relevance
“…Cross-sectional studies from Western countries have reported alcohol intake to be strongly associated with increased ALT levels (Ruhl and Everhart, 2005;Ioannou et al, 2006). However, other studies did not confirm such a relationship between alcohol intake and ALT level (Nakamura et al, 1998;Adams et al, 2008).…”
Section: Introductionmentioning
confidence: 67%
“…Cross-sectional studies from Western countries have reported alcohol intake to be strongly associated with increased ALT levels (Ruhl and Everhart, 2005;Ioannou et al, 2006). However, other studies did not confirm such a relationship between alcohol intake and ALT level (Nakamura et al, 1998;Adams et al, 2008).…”
Section: Introductionmentioning
confidence: 67%
“…ALT is not an ideal marker for either the diagnosis of NAFLD or distinguishing simple steatosis from non-alcohol steatohepatitis (NASH) [13]. This was also verified in the NHANES survey where approximately 10 % of subjects have elevations of ALT and AST [14] with fatty liver being one of the most common causes [15].…”
Section: Transaminasesmentioning
confidence: 99%
“…NAFLD is now considered to be the most common cause of serum ALT elevations in the US population (9). Previous studies have shown that there is familial clustering of factors that may predispose to the development of NAFLD, NASH, and cryptogenic cirrhosis (18,19,26).…”
Section: In the Context Of Current Literaturementioning
confidence: 99%
“…In addition, there are strong ethnic associations to elevated serum ALT levels and NAFLD (12,15,16). Familial clustering of fatty liver, NASH and cryptogenic cirrhosis has been reported, further suggesting that genetic factors may play a role in the pathogenesis of NAFLD (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation